2009
DOI: 10.1111/j.1600-0838.2009.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise program for prevention of groin pain in football players: a cluster-randomized trial

Abstract: Groin injuries cause major problems in sports and particularly in football. Exercise is effective in treating adductor-related groin pain, but no trials have been published regarding the specific prevention of groin pain or prevention specifically targeting overuse injuries in sport using exercise programs. We performed a cluster-randomized trial including 55 football clubs representing 1211 players. The clubs were randomized to an exercise program aimed at preventing groin injuries (n=27) or to a control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
132
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(145 citation statements)
references
References 32 publications
6
132
2
5
Order By: Relevance
“…Previously, a randomised controlled trial (RCT) have shown that a comprehensive strengthening programme, supervised by physiotherapists, including focused hip-adductor strengthening is highly effective in the treatment of long-standing adductor-related groin pain 35. The preventive effect of a programme based on this treatment, supervised by the team coach, has also been investigated in an RCT and found a 31% reduction of groin injuries in a soccer population, however, not significant 36. The lack of a significant effect of this programme have been suggested to be the result of different factors, such as an insufficient sample size, and a possible lack of compliance of the soccer players to perform the programme as prescribed, regarding the intended frequency and intensity 36.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a randomised controlled trial (RCT) have shown that a comprehensive strengthening programme, supervised by physiotherapists, including focused hip-adductor strengthening is highly effective in the treatment of long-standing adductor-related groin pain 35. The preventive effect of a programme based on this treatment, supervised by the team coach, has also been investigated in an RCT and found a 31% reduction of groin injuries in a soccer population, however, not significant 36. The lack of a significant effect of this programme have been suggested to be the result of different factors, such as an insufficient sample size, and a possible lack of compliance of the soccer players to perform the programme as prescribed, regarding the intended frequency and intensity 36.…”
Section: Discussionmentioning
confidence: 99%
“…The preventive effect of a programme based on this treatment, supervised by the team coach, has also been investigated in an RCT and found a 31% reduction of groin injuries in a soccer population, however, not significant 36. The lack of a significant effect of this programme have been suggested to be the result of different factors, such as an insufficient sample size, and a possible lack of compliance of the soccer players to perform the programme as prescribed, regarding the intended frequency and intensity 36. To document the exact compliance and ensure correct performance of the hip-adductor strengthening programme, in the present study, the programme was supervised by a physiotherapist, in each of the participating clubs.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Furthermore, a number of studies have indicated that specific targeted strengthening programs of the hamstring and adductor musculature can reduce the incidence of hamstring injuries and adductor muscle injuries. [18][19][20][21] The results of the present study indicate that a 5-week neck strengthening program improved sagittal and frontal plane isometric neck strength in a cohort of professional rugby union players. Of particular importance was the fact that the improvements in isometric neck strength exceeded recently published minimum detectable change values for each muscle contraction evaluated.…”
Section: Discussionmentioning
confidence: 66%
“…Holmich et al (2010) conducted a study to determine the effects of an exercise program, including strengthening, coordination and core stability during 25 warm up, on the incidence of groin injuries. 28 No significant effect of the intervention on the rate of groin injuries was found. Pope and colleagues (1998) found no evidence for the preventive effects of pre-exercise stretching on the incidence of lower extremity injury, including Achilles…”
Section: Resultsmentioning
confidence: 89%